Chitosan oligosaccharide derivatives as green corrosion inhibitors for P110 steel in a carbon-dioxide-saturated chloride solution. (1st January 2019) - Cui, Guodong; Guo, Jixiang; Zhang, Yu; Zhao, Qing; Fu, Shunkang; Han, Tong; Zhang, Shiling; Wu, Yanhua
Highlights: We synthesized amphiphilic oligosaccharide derivatives as green corrosion inhibitors. FTIR and NMR results indicate successful preparation of oligosaccharide derivatives. Gravimetric, electrochemical, AFM and SEM-EDX methods were used for investigation. Amphiphilic oligosaccharide derivatives have a good corrosion inhibition efficiency. Abstract: Two chitosan oligosaccharide derivatives (PHC and BHC) were synthesized for use as corrosion inhibitors. They were characterized using Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). The inhibition efficiency of PHC and BHC on P110 steel corrosion in a 3.5 wt.% NaCl CO2 -saturated solution at 80℃ was studied using gravimetric measurement, scanning electron microscopy (SEM), atomic force microscopy (AFM), electrochemical analysis, and quantum chemical calculation. The results indicated that inhibition efficiency increased with increasing concentration of inhibitor. Energy dispersive X-ray (EDX), contact angle, and electrochemical impedance spectroscopy (EIS) measurements showed that the inhibitors had been successfully adsorbed to the surface of the P110 steel. The results of potentiodynamic polarization indicated that both compounds were mixed-type inhibitors.